Polsko-niemieckie stosunki gospodarcze ze szczególnym uwzględnieniem obszaru pogranicza - Adamczuk, Franciszek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The paper aims to characterize and evaluate Polish-German bilateral relations - particularly the one around the frontier area. Starting with local government and ending with institutional one, the forms and scope of co-operation have been presented. The study ends with conclusions and recommendations, which can benefit and develop these relations in the future. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 15-21